1994
DOI: 10.1111/j.1600-0447.1994.tb05912.x
|View full text |Cite
|
Sign up to set email alerts
|

Sociology in the context of social psychiatry

Abstract: The author addresses various aspects of the interface between sociology and social psychiatry, among them the labelling process related to mental deviance, problems related to diagnosis and social ethology. The need for interdisciplinary work is emphasized, not least in the context of prevention. It is underlined that effective preventive measures can precede the full causal elucidation of a disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Two potent sources of confusion about the idea of mental illness exist in the public mind. First, mental illness has to be distinguished from other causes of social deviance also involving distress and abnormal behaviour [17]. Mental illness, eccentricity and badness are different in meaning.…”
Section: Concepts Of Mental Illness and Mental Healthmentioning
confidence: 99%
“…Two potent sources of confusion about the idea of mental illness exist in the public mind. First, mental illness has to be distinguished from other causes of social deviance also involving distress and abnormal behaviour [17]. Mental illness, eccentricity and badness are different in meaning.…”
Section: Concepts Of Mental Illness and Mental Healthmentioning
confidence: 99%
“…8 Fears of reductionism abound from all quarters. 9,10 Yet, as sciences work towards discoveries of disease and pathology, at the same time there remains a deep suspicion of medicine, doctors, brain sciences, and the over-worked ‘medical model’. 11 The fears are partly to do with choice and power, in vulnerable and disempowered patients, and with concerns about the influence of the pharmaceutical industry, but also that reductionism may follow to render emotions, distress, human suffering and moral fractures as surface phenomena that are explained away as deriving from core pathologies of brain rather than mind; and thus, this line of reasoning gives rise to the suspicion that people will be treated inhumanely and their citizenship rights and entitlements may be violated.…”
mentioning
confidence: 99%
“…All of this said, as much as greater sophistication in research will further our understanding, we need not sit back and wait for this to accrue before advocating change at policy and service delivery levels. As Brian Cooper (Cooper, 1992) commented nearly 20 years ago in relation to the same issue: ‘the history of public-health epidemiology, from cholera to bronchial carcinoma, has repeatedly demonstrated that effective preventive measures can precede the full causal elucidation of a disease’ (p. 597).…”
mentioning
confidence: 99%